Quadriceps Activation After Anterior Cruciate Ligament Reconstruction: The Early Bird Gets the Worm! - Ayrton MOIROUX--SAHRAOUI; Florian FORELLI; Jean MAZEAS; Alexandre JM RAMBAUD; Andreas BJERREGAARD; Jérôme RIERA (International Journal of Sports Physical Therapy)
Arthrogenic Muscle Inhibition (AMI) is a phenomenon observed in individuals with joint injury or pathology, characterized by a reflexive inhibition of surrounding musculature, altered neuromuscular control, and compromised functional performance. After anterior cruciate ligament reconstruction (ACLR) one of the most obvious consequences of AMI is the lack of quadriceps activation and strength. Understanding the underlying mechanisms of AMI is crucial for developing effective therapeutic interventions. The surgical procedure needed to reconstruct the ACL has biochemical et physiological consequences such as inflammation, pain, and altered proprioception. These alterations contribute to the development of AMI. Therapeutic interventions aimed at addressing AMI encompass a multidimensional approach targeting pain reduction, inflammation management, proprioceptive training, and quadriceps activation. Early management focusing on pain modulation through modalities like ice, compression, and pharmacological agents help mitigate the inflammatory response and alleviate pain, thereby reducing the reflexive inhibition of quadriceps.